الدعوة في الفكر الإستشراقي كتاب - الدعوة إلى الإسلام - لأرنولد توماس ــــ - بن علي, كريمة; ليحيو, مريم (University of eloued جامعة الوادي, 2021)
لقد واجهت الدعوة منذ بزوغ فجرها إلى يومنا هذا عدة تحديات ,ويعد الاستشراق من بين هذه التحديات ولقد ظهر العديد من المستشرقين ومن بينهم المستشرق الانجليزي ارنولد توماس ويعد من المستشرقين المنصفين والمتعاطفين مع الإسلام والمسلمين ,وقد بدا ذلك واضحا وجليا في كتابه الدعوة إلى الإسلام والمتصفح لهذا الكتاب سيلحظ ذلك ,حيث بذل توماس جهوده في اعطاء الصورة الحقيقية للدعوة والاسلام وتصحيحها في المنظور الاستشراقي وفند كل الاباطيل والشبهات التي اثيرت ضد الدعوة ,فما بذله توماس يعتبر من الجهود العلمية والتاريخة من خلال تتبعه لانتشار الدعوة في كل أقطار الارض Since its dawning, the da’wa has faced several challenges, and Orientalism is among these challenges. Many orientalists, including the English orientalist Arnold Thomas, have been purified. He is considered one of the just orientalists and sympathizers with Islam and Muslims. This was clear and evident in his book The Call to Islam and the Browser. For this book it will be noted that, as Thomas made his efforts to give the true picture of the call and Islam and correct it from the orientalist perspective and refuted all the falsehoods and suspicions that were raised against the call, what Thomas made is considered a scientific and historical effort by tracing the spread of the call in all countries of the earth
دعوة واعلام
Keywords: الدعوة الاسلامية, الإستشراق, افريقيا, السوادن الغربي, البربر; Islamic call . Orientalism . Africa.Western Sudan . Berber